Effect of Rh- Positive Blood Group on Distortion Product Otoacoustic Emission Input–Output Function - Kumaar, Bhuvaneswari; Karupaiah, Kamalakannan; Ramachandran, Sundaresan; Iruthayam, Celcia; Sabu, Meghana; Prabhu, Prashanth (Indian journal of otolaryngology, and head, and neck surgery, 2024)
The blood group system of human beings can impact the health and auditory system. There are correlations between various audiological test findings and blood groups. Studies have shown that persons with the O blood group have reduced resonance frequency of the middle ear and amplitude of otoacoustic emissions. Therefore, Otoacoustic emissions (OAE) results could be different across blood groups. The current study aimed to determine the difference in Distortion product otoacoustic emission input–output function in persons with varying groups of blood. A total of sixty college-going young female adults, aged between 18 and 25 years, participated in the current study. They were divided into four groups, each with 15 participants based on the blood group type (A, B. AB. O). The subjects underwent Distortion product otoacoustic emission (DPOAE) input–output function on the following frequencies: 703 Hz,1060 Hz,1416 Hz,2114 Hz,2827 Hz,4243 Hz, and 5645 Hz. The analysis showed no significant difference in the area and slope of the Distortion product otoacoustic emission input–output function at all frequencies. Thus, the study’s result shows no effect of the blood group on Distortion product otoacoustic emission input- output function.